The Effect of Endorphin Message Technique Towards the Decrease of Pain at the First Childbirth in BPM and Society Health Center Palembang - Azelea, A; Vasra, E; Kadir, A (KnE Life Sciences, 2019)
One of the treatments for Pregnant Women that is still not widely known, is Endorphin Massage. The aim of the study was to determine the effect of endorphin massage on the first stage of childbirth. The design of quasi-experimental research are with pre and post-test designs. This research was conducted at BPM Husniyati Plaju, and Gandus Society Health Center, Palembang. The population in this research were all normal maternal mothers at BPM Husniyati Plaju Palembang in 2016. The samples are 20 people. The research result showed before the intervention, the respondent’s pain scale was mild pain 8 (40%), medium 12 (60%) and after intervention the respondent pain scale was mild pain 19 (95%) and severe pain 1 (5%). The childbirth pain intensity before p value = 0.117 and pain intensity after p value = 0.429, there was no effect of endorphin massage on the pain intensity in the first stage of normal childbirth, the results of T test showed 7.483 with p-value = 0,000 (p value <α 0.05) there was a significant difference in Endorphin massage intervention. The childbirth pain intensity before p value = 0.117 and pain intensity after p value = 0.429, there was no effect of endorphin massage on the intensity of first stage pain but the T test results showed 7.483 (p value <α 0.05) there were significant differences in Endorphin massage intervention. Keywords: Endorphin massage, pain, childbirth